Serotonin Regulates Lipogenesis and Endoplasmic Reticulum Stress in Alcoholic Liver Disease - Inseon Hwang; Jung Eun Nam; Wonsuk Choi; Won Gun Choi; Eunji Lee; Hyeongseok Kim; Young-Ah Moon; Jun Yong Park; Hail Kim (Diabetes & Metabolism Journal, 2025)
Background Serotonin (5-hydroxytryptamine [5-HT]) is a monoamine neurotransmitter that has various functions in central and peripheral tissues. While 5-HT is known to regulate various biological processes in liver, direct role of 5-HT and its receptors, especially 5-HT receptor 2A (HTR2A) and HTR2B, in development and progression of alcoholic liver disease (ALD) in vivo is not well understood. Methods Blood 5-HT level was measured from both human ALD patients and ethanol (EtOH) diet-fed mouse models. Gut-specific tryptophan hydroxylase 1 (Tph1) knockout mice, liver-specific Htr2a knockout mice, and liver-specific Htr2b knockout mice were fed with EtOH diet. Then we evaluated liver damage, hepatic steatosis, endoplasmic reticulum (ER) stress, and inflammation. Results Blood 5-HT concentrations are increased in both humans and mice with ALD. Both gut-specific Tph1 knockout and liver-specific Htr2a knockout mice are resistant to steatosis by down-regulating lipogenic pathways in liver of chronic EtOH diet-fed mice. Moreover, genetic inhibition of both gut-derived serotonin (GDS) synthesis and hepatic HTR2A signaling prevents ER stress in liver of chronic EtOH diet-fed mice. Additionally, we found that ablation of HTR2A signaling protects against disease progression by attenuating liver injury and inflammation in chronic plus binge EtOH diet-fed mice. Also, inhibiting HTR2A signaling ameliorates alcohol-induced liver injury and ER stress in an acute EtOH diet-fed mice model. Conclusion GDS directly regulates lipogenesis and ER stress via signaling through hepatic HTR2A in the context of ALD. Inhibiting HTR2A signaling protects against alcohol-induced steatosis, liver injury and disease progression in various ALD mouse models and may also provide a novel therapeutic strategy for ALD.